Growth and yield response of three lettuce varieties (Lactuca sativa L.) with different lighting durations in hydroponic cultivation - Wijaya, Acep Atma; Sukmasari, Miftah Dieni; Nugraha, Dadan Ramdani; Harti, Adi Oksifa Rahma; Tifani, Aaz Azamudin; Sukma, Robi Bastian; Andayani, Sri Ayu (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Lettuce ( Lactuca sativa L.) is a popular vegetable plant in Indonesia. This is because the demand for lettuce continues to increase and lettuce plants can be planted with a hydroponic system that is currently in great demand by the community, especially generation Z (Gen Z). In meeting the demand for lettuce, lettuce is planted hydroponically. Planting in a hydroponic system often does not pay attention to the intensity of light that can be received by plants due to the shade from the GreenHouse or UV plastic used, so that plants cannot grow optimally. The purpose of this study was to find the most suitable lettuce varieties planted hydroponically at various irradiation times as well as the most appropriate long light for lettuce plant growth and to analyze the relationship between characters with the yield for indirect selection. Methods: The study was conducted at the GreenHouse Arsy Hydroponic using a Completely Randomized Design (CRD) factorial pattern. 3 lettuce varieties and 4 long light treatments were the treatments in this study. The relationship between characters was analyzed using correlation analysis. Results: The results of the study showed that the Cos and Batavia varieties can generally be used for planting with a light duration of more than 12 hours compared to the Oakleaf variety. Light duration of less than 12 hours is not recommended because it will cause the plant height to be higher, especially for the Oakleaf variety. In the indirect selection process to obtain high-yielding varieties in the hydroponic system by providing light duration and varieties can be selected from the characteristics of the number of leaves, leaf width and root length which have a significant positive correlation. Conclusion: The results of the study showed that selecting the appropriate variety can increase optimal crop yields. Information on the relationship between plant characteristics is very important to increase the effectiveness of selection.